A pathologic review of ophthalmic tumors in Kano, Northern Nigeria - Umar, Ali; Ochicha, Ochicha; Iliyasu, Yawale (Nigerian Journal of Basic and Clinical Sciences, 2026)
Background and Objective: Tumors of eye and ocular adnexa are reported to be common in Africa, but no formal study has been conducted here in Kano, the largest Northern Nigerian city. This study is a documentation of the pattern of ophthalmic tumors in our locality.Materials and Methods: This was a 12-year (1999-2010 inclusive) retrospective study of all orbito-ocular neoplasms diagnosed at the pathology department of a teaching hospital.Results: 438 ophthalmic tumors were diagnosed during the study period, of which 79.7% were malignant and 20.3% benign. Males were slightly more preponderant with M/F ratio of 1.3:1. Retinoblastoma and conjunctival squamous carcinoma were the commonest tumors respectively comprising 44.5% and 18.9%. These two ocular malignancies also largely accounted for the bimodal age distribution peaks of ophthalmic cancer in the 1stand 4thdecades. Conjunctival squamous papilloma and hemangioma were the most prevalent benign ophthalmic tumors.Conclusion: Our findings were broadly similar to most other Nigerian and African studies but significantly at variance with those of the western world.
Keywords: Conjunctival carcinoma; eye tumors; Nigeria; retinoblastoma